Recent Amendments To The Housing Developers (Control & Licensing) Act, 1966 And The New Housing Developers (Control & Licensing) Regulations, 1989 - Teo, Keang Sood (Journal of Malaysian and Comparative Law, 2019)
Recent Amendments To The Housing Developers (Control & Licensing) Act, 1966 And The New Housing Developers (Control & Licensing) Regulations, 1989